Design and Implementation Issues in Longitudinal Research - Ludlow, Larry H; Pedulla, Joseph; Enterline, Sarah; Mitescu Reagan, Emilie; Cannady, Mac; Chappe, Stephanie (Education Policy Analysis Archives, 2011)
<!–[if gte mso 9]> 72 1024x768 <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–>To meet demands for accountability, most schools and departments of education at institutions of higher education (IHEs) gather information on their current students and graduates. This paper describes issues and considerations when designing a longitudinal data collection and management system, drawing on seven years’ experience developing such a system. The recommendations provided stem from an attempt to use data collected for accountability more broadly to look at the specific issue of teacher retention/attrition. Recommendations include: maintain a stable staff, including a skilled data manager; attend fastidiously to record keeping and documentation; if measuring change, minimize change in measures; and gather data on multiple cohorts to cross-validate findings.